Dampak Kebijakan Harga Pembelian Petani Gabah terhadap Kesejahteraan Petani: Suatu Simulasi - Putri, Eka Intan K.; Novindra, Novindra; Nuva, Nuva (Jurnal Ekonomi dan Pembangunan Indonesia, 2013)
To control supply and demand rice and increase income to farmer, Government assigned a rice purchasing policy. This study apply 2SLS model with time series data 1971-2009 to simulate and forecast the impact of rice purchasing policy on farmer welfare. The responses of rice real price at farmers' level towards the changes of real price of government purchases and rice production is elastic in the long term. Demand of rice is significantly influenced by the price of rice, population, and demand for rice at t - 1. The increasing of rice purchasing price (HPP) on grain at 9.54% and 15% lead to an increasing of farmer's surplus IDR163,512,308,700 and IDR257,292,128,790.